The Political Vision of the Divine Comedy - Ferrante, Joan M. (Book collections on Project MUSE., 2014)
Joan Ferrante analyzes the Divine Comedy in terms of public issues, which continued foremost in Dante's thinking after his exile from Florence. Professor Ferrante examines the political concepts of the poem in historical context and in light of the political theory and controversies of the period. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts.